The effect of honey consumption on muscle glycogen resynthesis following exercise: a review of the literature - Pajak, Julia; Kamosińska, Anna; Sławatyniec, Olga; Sobieraj, Wiktoria; Łuniewska, Wiktoria; Modrzyk, Marta; Majda, Antoni (Journal of Education, Health and Sport, 2026)
Glycogen is the primary form of carbohydrate storage in the human body and a key energy substrate during exercise. Its depletion contributes to fatigue and reduced exercise performance; therefore, effective post-exercise glycogen resynthesis is essential for recovery in athletes. Honey, due to its unique composition of glucose and fructose, may support the restoration of both muscle and liver glycogen stores while providing a more stable glycaemic response than pure glucose. Moreover, honey contains antioxidant and anti-inflammatory compounds that may reduce oxidative stress and support immune function after intense physical activity. Available studies indicate that honey demonstrates similar effectiveness to commercial carbohydrate supplements such as glucose, sucrose, and maltodextrin in supporting glycogen replenishment and post-exercise recovery. Some evidence also suggests beneficial effects on delayed-onset muscle soreness (DOMS) and exercise performance. Despite promising findings, further studies are required to establish optimal dosing strategies and evaluate the long-term effects of honey supplementation in sports nutrition. Background: Muscle glycogen depletion during exercise impairs physical performance and accelerates fatigue. Effective glycogen resynthesis is therefore a crucial element of post-exercise recovery. Aim: The aim of this study was to review the effects of honey consumption on muscle glycogen resynthesis and post-exercise recovery. Materials and methods: A review of the available literature concerning glycogen metabolism, recovery, and honey supplementation in physically active individuals was conducted. Summary: Honey may effectively support glycogen replenishment and recovery due to its carbohydrate composition and antioxidant properties. Conclusions: Honey appears to be a promising natural alternative to commercial sports supplements used during post-exercise recovery.